ANALISIS PERAMALAN TABUNGAN HAJI PADA BANK BJB SYARIAH KANTOR CABANG PEMBANTU JEMBATAN MERAH BOGOR DI MASA PANDEMI COVID-19. - Anwar, Miftakhul; Nurlaelia, Widia Afria; Thantawi, Tubagus Rifqy (SAHID BANKING JOURNAL, 2023)
Along with developments and people’s needs for banking services, Islamic bank produts are becoming more numerous and can accommodate people’s needs for banking services, one of which is hajj savings products and this study aims to analyze the forecasting of hajj savings at BJBS KCP Jembatan Merah Bogor bank during a pandemic Covid-19 in 2022-2023. The data produced by researchers are primary data based on data obtained from banks in the 2020-2021 period and secondary data used as a basis for comparison and discussion of past conditions and conditions to be forecasted. This research uses quantitative methods with time series analysis with a descriptive study approach, the types of forecasting used in this study are linear trends, quadratic trends and exponential trends. The results of this forecasting analysis show that based on the MSE value obtained by quadratic trends produce the smallest value, which means it has the lowest error tendency. Forecasting using quadratic trends predicts an increase in prospective Hajj savings customers at Bank BJBS KCP Jembatan Merah Bogor by an average of 12% in 2022 while the average increase in prospective customers in 2023 is 6%.